2017
DOI: 10.1002/pbc.26560
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in treatment abandonment in pediatric patients with cancer in Guatemala

Abstract: Background: Treatment refusal and abandonment are major causes of treatment failure for children with cancer in low-and middle-income countries (LMICs), like Guatemala. This study identified risk factors for and described the intervention that decreased abandonment. younger age (P = 0.017) and earlier year of diagnosis (P < 0.001). Indigenous race/ethnicity (P = 0.002) was associated with increased risk of abandonment alone. Abandonment correlated with decreased overall survival: 0.57 ± 0.02 (survival ± standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 27 publications
4
41
2
Order By: Relevance
“…Similarly, Vasquez et al, in 2018 in Peru, found a significant association between a higher risk of abandonment in patients with retinoblastoma . We did not find a higher frequency of treatment abandonment among patients younger than five years at diagnosis, as has been reported in other studies . More recently, Vasquez et al found no association between age and risk of treatment abandonment in Peru …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similarly, Vasquez et al, in 2018 in Peru, found a significant association between a higher risk of abandonment in patients with retinoblastoma . We did not find a higher frequency of treatment abandonment among patients younger than five years at diagnosis, as has been reported in other studies . More recently, Vasquez et al found no association between age and risk of treatment abandonment in Peru …”
Section: Discussionsupporting
confidence: 83%
“…However, it has been reported that Chinese females had a higher risk of refusing treatment and treatment abandonment compared with males . In addition, Alvarez et al reported an association between indigenous race/ethnicity and treatment abandonment in Guatemala, suggesting that race/ethnicity may be a surrogate for another factor such as cultural beliefs surrounding the attitudes toward Western medicine and alternative treatments. Perhaps this did not occur in our cohort due to the intense miscegenation of the Brazilian people and the consequent difficulty in defining ethnicities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determinants of TxA in our study (socioeconomic factors, perceived prognosis of disease, concerns about toxicity, and preference for TCAM) are very similar to those worldwide, as established in a global online survey, a systematic review, and other reports . Strategies to reduce abandonment are being studied and increasingly reported . Most centers have adopted overlapping strategies that stem from an increased understanding of the deficiencies common to most LMIC settings.…”
Section: Discussionsupporting
confidence: 56%
“…Most centers have adopted overlapping strategies that stem from an increased understanding of the deficiencies common to most LMIC settings. These usually tend to focus on one or more aspects of support and include setting up of local foundations, enhanced psychosocial support, education of families, subsidized or free treatment, food, transport, and lodging for families, and development of adapted treatment protocols, all of which have been found to decrease rates of TxA . A few reports have also focused on surveillance of treatment adherence and prospective tracking of patients, coupled with timely intervention .…”
Section: Discussionmentioning
confidence: 99%